2017
DOI: 10.1051/0004-6361/201730396
|View full text |Cite
|
Sign up to set email alerts
|

Overall properties of theGaiaDR1 reference frame

Abstract: Aims. The first Gaia data release (Gaia DR1) provides 2 191 ICRF2 sources with their positions in the auxiliary quasar solution and five astrometric parameters -positions, parallaxes, and proper motions -for stars in common between the Tycho-2 catalogue and Gaia in the joint Tycho-Gaia astrometric solution (TGAS). We aim to analyze the overall properties of Gaia DR1 reference frame. Methods. We compare quasar positions of the auxiliary quasar solution with ICRF2 sources using different samples and evaluate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…From the column dz in Table 2, one can clearly find a significant bias in both ICRF2 and gsf2016a catalogs. The bias was estimated to be of 78 ∼ 152 µas between ICRF2 and Gaia DR1 catalogs, which agrees with the declination bias of about −0.1 mas as reported in Mignard et al (2016) and later confirmed in our previous work (Liu et al 2017). For gsf2016a, dz was estimated to be smaller in comparison, strictly beneath 100 µas for all five groups, especially for the "Defining" group which yielded zero bias.…”
Section: Representations Of the Systematicssupporting
confidence: 90%
See 1 more Smart Citation
“…From the column dz in Table 2, one can clearly find a significant bias in both ICRF2 and gsf2016a catalogs. The bias was estimated to be of 78 ∼ 152 µas between ICRF2 and Gaia DR1 catalogs, which agrees with the declination bias of about −0.1 mas as reported in Mignard et al (2016) and later confirmed in our previous work (Liu et al 2017). For gsf2016a, dz was estimated to be smaller in comparison, strictly beneath 100 µas for all five groups, especially for the "Defining" group which yielded zero bias.…”
Section: Representations Of the Systematicssupporting
confidence: 90%
“…Comparing the results of different groups in the same catalog, however, some inconsistencies are presented. For the ICRF2 catalog, the relative orientation angles for groups "North" and "South" have opposite signs, as found in Liu et al (2017). Using the new gsf2016a data, we attained similar results, indicating that there are possible zonal deformations between VLBI and Gaia DR1 catalogs.…”
Section: Representations Of the Systematicssupporting
confidence: 73%
“…Indeed, the mean distance for the sample of stars used in obtaining the solution (6) is 2.0 kpc; then ω 1 = 0.051 ± 0.016 mas yr −1 and ω 2 = 0.034 ± 0.021 mas yr −1 . We see that here ω 2 differs from the result of Liu et al (2017) by an order of magnitude.…”
Section: Rotation Around the Z Axismentioning
confidence: 58%
“…Liu et al (2017) performed a kinematic analysis of ∼23 000 K-M giants from the TGAS catalogue(Brown et al 2016) based on the Ogorodnikov-Milne model and found a nonzero component ω 2 = −0.38 ± 0.15 mas yr −1 (rotation around the Galactic y axis). They interpreted this as a possible residual rotation in the TGAS frame or the presence of problems in the kinematic model.…”
mentioning
confidence: 99%
“…However, there are few research materials on self-lubricating coatings in China. In the year of 1983, the first MoS 2 self-lubricating coatings prepared by liquid dope was studied by Liu of the Institute of Coatings, however, the coatings were not applied to sliding bearings [38]. The sliding bearing surface coating technology of China started late, and it is still a new technology.…”
Section: Liquid Dope Of Sprayingmentioning
confidence: 99%